Advancing Aeronautical Safety: A Review of NASA's Aviation Safety-Related Research Programs - Transportation Research Board; National Research Council (The National Academies Press, 2010)
Advancing the state of aviation safety is a central mission of the National Aeronautics and Space Administration (NASA). Congress requested this review of NASA's aviation safety-related research programs, seeking an assessment of whether the programs have well-defined, prioritized, and appropriate research objectives; whether resources have been allocated appropriately among these objectives; whether the programs are well coordinated with the safety research programs of the Federal Aviation Administration; and whether suitable mechanisms are in place for transitioning the research results into operational technologies and procedures and certification activities in a timely manner. Advancing Aeronautical Safety contains findings and recommendations with respect to each of the main aspects of the review sought by Congress. These findings indicate that NASA's aeronautics research enterprise has made, and continues to make, valuable contributions to aviation system safety but it is falling short and needs improvement in some key respects.
Keywords: Space and Aeronautics; Earth Sciences

Review of the WATERS Network Science Plan - National Research Council (The National Academies Press, 2010)
One of the most critical issues facing the United States today is the proper management of our water resources. Water availability and quality are changing due to increasing population, urbanization, and land use and climate change, and shortages in water supply have been increasing in frequency in many parts of the country. The National Science Foundation (NSF) has entertained the Water and Environmental Research Systems (WATERS) Network as one possible initiative whereby NSF could provide the advances in the basic science needed to respond effectively to the challenge of managing water resources. The WATERS Network, a joint initiative of the Engineering, the Geosciences, and the Social, Behavioral and Economic Sciences directorates at NSF, is envisioned as an integrated national network of observatories and experimental facilities supporting research, outreach, and education on large-scale, water-related environmental problems. The proposed observatories would provide researchers with access to linked sensing networks, data repositories, and computational tools connected through high-performance computing and telecommunications networks. This book, the final of a series about the WATERS project, provides a more detailed review of the Science Plan and provides advice on collaborating with other federal agencies.
Keywords: Earth Sciences

NOAA's Education Program: Review and Critique - National Research Council (The National Academies Press, 2010)
There is a national need to educate the public about the ocean, coastal resources, atmosphere and climate. The National Oceanic and Atmospheric Administration (NOAA), the agency responsible for understanding and predicting changes in the Earth's environment and conserving and managing coastal and marine resources to meet the nation's economic, social and environmental needs, has a broad mandate to engage and coordinate education initiatives on these topics. Since its creation in 1970, the NOAA has supported a variety of education projects that cover a range of topics related to the agency's scientific and stewardship mission. NOAA uses formal and informal learning environments to enhance understanding of science, technology, engineering and mathematics (STEM) and to advance environmental education. The work of this agency overlaps and compliments the missions of other federal agencies, institutions of higher education, private and nonprofit organizations. Coordination among these agencies and organizations has been challenging. Limited education resources and the inherently global nature of NOAA's mission make strategic partnerships critical in order for the agency to accomplish its goals. Additionally, clear education goals, planning, and strategic use of resources are critical aspects for effective partnerships. NOAA's Education Program: Review and Critique provides a summary of the national education context for NOAA's role in education which is twofold: first is to advance the environmental literacy of the nation, and second is to promote a diverse workforce in ocean, coastal, Great Lakes, atmospheric and climate sciences. The book also describes the strengths and weaknesses of the education strategic plan, the education evaluation approach of the agency and strategies for improving the evaluation process.
Keywords: Earth Sciences; Education

Alternate Strategies for Safety Improvement Investments - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Results Digest 345: Alternate Strategies for Safety Improvement Investments explores the “black spot” analysis and “systematic” methods currently being used by states to help make decisions on the allocation of safety resources.
Keywords: Transportation and Infrastructure

Review of the Department of Homeland Security's Approach to Risk Analysis - National Research Council (The National Academies Press, 2010)
The events of September 11, 2001 changed perceptions, rearranged national priorities, and produced significant new government entities, including the U.S. Department of Homeland Security (DHS) created in 2003. While the principal mission of DHS is to lead efforts to secure the nation against those forces that wish to do harm, the department also has responsibilities in regard to preparation for and response to other hazards and disasters, such as floods, earthquakes, and other "natural" disasters. Whether in the context of preparedness, response or recovery from terrorism, illegal entry to the country, or natural disasters, DHS is committed to processes and methods that feature risk assessment as a critical component for making better-informed decisions. Review of the Department of Homeland Security's Approach to Risk Analysis explores how DHS is building its capabilities in risk analysis to inform decision making. The department uses risk analysis to inform decisions ranging from high-level policy choices to fine-scale protocols that guide the minute-by-minute actions of DHS employees. Although DHS is responsible for mitigating a range of threats, natural disasters, and pandemics, its risk analysis efforts are weighted heavily toward terrorism. In addition to assessing the capability of DHS risk analysis methods to support decision-making, the book evaluates the quality of the current approach to estimating risk and discusses how to improve current risk analysis procedures. Review of the Department of Homeland Security's Approach to Risk Analysis recommends that DHS continue to build its integrated risk management framework. It also suggests that the department improve the way models are developed and used and follow time-tested scientific practices, among other recommendations.
Keywords: Conflict and Security Issues

Review of the Research Program of the FreedomCAR and Fuel Partnership: Third Report - National Research Council (The National Academies Press, 2010)
The public-private partnership to develop vehicles that require less petroleum-based fuel and emit fewer greenhouse gases should continue to include fuel cells and other hydrogen technologies in its research and development portfolio. The third volume in the FreedomCAR series states that, although the partnership's recent shift of focus toward technologies that could be ready for use in the nearer term—such as advanced combustion engines and plug-in electric vehicles—is warranted, R&D on hydrogen and fuel cells is also needed given the high costs and challenges that many of the technologies must overcome before widespread use. The FreedomCAR (Cooperative Automotive Research) and Fuel Partnership is a research collaboration among the U.S. Department of Energy, the United States Council for Automotive Research - whose members are the Detroit automakers—five major energy companies, and two electric utility companies. The partnership seeks to advance the technologies essential for components and infrastructure for a full range of affordable, clean, energy efficient cars and light trucks. Until recently, the program primarily focused on developing technologies that would allow U.S. automakers to make production and marketing decisions by 2015 on hydrogen fuel cell-powered vehicles. These vehicles have the potential to be much more energy-efficient than conventional gasoline-powered vehicles, produce no harmful tailpipe emissions, and significantly reduce petroleum use. In 2009, the partnership changed direction and stepped up efforts to advance, in the shorter term, technologies for reducing petroleum use in combustion engines, including those using biofuels, as well as batteries that could be used in plug-in hybrid-electric or all electric vehicles.
Keywords: Transportation and Infrastructure; Energy and Energy Conservation

A Database for a Changing Economy: Review of the Occupational Information Network (O*NET) - National Research Council (The National Academies Press, 2010)
Information about the characteristics of jobs and the individuals who fill them is valuable for career guidance, reemployment counseling, workforce development, human resource management, and other purposes. To meet these needs, the U.S. Department of Labor (DOL) in 1998 launched the Occupational Information Network (O*NET), which consists of a content model—a framework for organizing occupational data—and an electronic database. The O*NET content model includes hundreds of descriptors of work and workers organized into domains, such as skills, knowledge, and work activities. Data are collected using a classification system that organizes job titles into 1,102 occupations. The National Center for O*NET Development (the O*NET Center) continually collects data related to these occupations. In 2008, DOL requested the National Academies to review O*NET and consider its future directions. In response, the present volume inventories and evaluates the uses of O*NET; explores the linkage of O*NET with the Standard Occupational Classification System and other data sets; and identifies ways to improve O*NET, particularly in the areas of cost-effectiveness, efficiency, and currency.
Keywords: Behavioral and Social Sciences; Industry and Labor; Surveys and Statistics

Progress Toward Restoring the Everglades: The Third Biennial Review - 2010 - National Research Council (The National Academies Press, 2010)
Although the progress of environmental restoration projects in the Florida Everglades remains slow overall, there have been improvements in the pace of restoration and in the relationship between the federal and state partners during the last two years. However, the importance of several challenges related to water quantity and quality have become clear, highlighting the difficulty in achieving restoration goals for all ecosystem components in all portions of the Everglades. Progress Toward Restoring the Everglades explores these challenges. The book stresses that rigorous scientific analyses of the tradeoffs between water quality and quantity and between the hydrologic requirements of Everglades features and species are needed to inform future prioritization and funding decisions.
Keywords: Environment and Environmental Studies; Earth Sciences

Enhancing Food Safety: The Role of the Food and Drug Administration - Institute of Medicine; National Research Council (The National Academies Press, 2010)
Recent outbreaks of illnesses traced to contaminated sprouts and lettuce illustrate the holes that exist in the system for monitoring problems and preventing foodborne diseases. Although it is not solely responsible for ensuring the safety of the nation's food supply, the U.S. Food and Drug Administration (FDA) oversees monitoring and intervention for 80 percent of the food supply. The U.S. Food and Drug Administration's abilities to discover potential threats to food safety and prevent outbreaks of foodborne illness are hampered by impediments to efficient use of its limited resources and a piecemeal approach to gathering and using information on risks. Enhancing Food Safety: The Role of the Food and Drug Administration, a new book from the Institute of Medicine and the National Research Council, responds to a congressional request for recommendations on how to close gaps in FDA's food safety systems. Enhancing Food Safety begins with a brief review of the Food Protection Plan (FPP), FDA's food safety philosophy developed in 2007. The lack of sufficient detail and specific strategies in the FPP renders it ineffectual. The book stresses the need for FPP to evolve and be supported by the type of strategic planning described in these pages. It also explores the development and implementation of a stronger, more effective food safety system built on a risk-based approach to food safety management. Conclusions and recommendations include adopting a risk-based decision-making approach to food safety; creating a data surveillance and research infrastructure; integrating federal, state, and local government food safety programs; enhancing efficiency of inspections; and more. Although food safety is the responsibility of everyone, from producers to consumers, the FDA and other regulatory agencies have an essential role. In many instances, the FDA must carry out this responsibility against a backdrop of multiple stakeholder interests, inadequate resources, and competing priorities. Of interest to the food production industry, consumer advocacy groups, health care professionals, and others, Enhancing Food Safety provides the FDA and Congress with a course of action that will enable the agency to become more efficient and effective in carrying out its food safety mission in a rapidly changing world.
Keywords: Food and Nutrition; Health and Medicine

Special Safety Concerns of the School Bus Industry - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 17: Special Safety Concerns of the School Bus Industry explores various safety issues faced by school bus operators, including how the issues are currently addressed, barriers to improvements, and suggestions for making improvements in the future.
Keywords: Transportation and Infrastructure

Older Commercial Drivers: Do They Pose a Safety Risk? - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 18: Older Commercial Drivers: Do They Pose a Safety Risk? explores age-related changes in the basic functional abilities needed to drive safely. The report is designed to help assist industry and labor practitioners in promoting safer commercial operations.
Keywords: Transportation and Infrastructure

Promoting Chemical Laboratory Safety and Security in Developing Countries - National Research Council (The National Academies Press, 2010)
There is growing concern about the possible use of toxic industrial chemicals or other hazardous chemicals by those seeking to perpetrate acts of terrorism. The U.S. Chemical Security Engagement Program (CSP), funded by the U.S. Department of State and run by Sandia National Laboratories, seeks to develop and facilitate cooperative international activities that promote best practices in chemical security and safe management of toxic chemicals, including: Partnering with host governments, chemical professionals, and industry to assess and fill gaps in chemical security abroad. Providing technical expertise and training to improve best practices in security and safety among chemical professionals and industry. Increasing transparency and accountability for dangerous chemical materials, expertise, and technologies. Providing opportunities for collaboration with the international professional chemical community. The Department of State called on the National Academies to assist in the CSP's efforts to promote chemical safety and security in developing countries.
Keywords: Math, Chemistry, and Physics; Environment and Environmental Studies; Conflict and Security Issues

Model Curriculum for Highway Safety Core Competencies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 667: Model Curriculum for Highway Safety Core Competencies presents course materials, including the instructor’s guide and student workbook, for a fundamental highway safety training course. The course is designed to address the core competencies highway safety practitioners should have or acquire. An accompanying CD-ROM includes a brochure and short Microsoft PowerPoint presentation for marketing the training course.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below. Help on Burning an .ISO CD-ROM Image Download the .ISO CD-ROM Image(Warning: This is a large and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively “TRB’) be liable for any loss or damage caused by the installation or operations of this product. TRB makes no representation or warrant of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Model Curriculum for Highway Safety Core Competencies - Transportation Research Board (The National Academies Press, 2010)
TRB's National Cooperative Highway Research Program (NCHRP) Report 667: Model Curriculum for Highway Safety Core Competencies presents course materials, including the instructor's guide and student workbook, for a fundamental highway safety training course. The course is designed to address the core competencies highway safety practitioners should have or acquire. An accompanying CD-ROM includes a brochure and short Microsoft PowerPoint presentation for marketing the training course. The CD-ROM is also available for download from TRB's website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below. Download the .ISO CD-ROM Image (Warning: This is a large and may take some time to download using a high-speed connection.) CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB') be liable for any loss or damage caused by the installation or operations of this product. TRB makes no representation or warrant of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Evaluation of Existing Roadside Safety Hardware Using Manual for Assessing Safety Hardware (MASH) Criteria - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Results Digest 349: Evaluation of Existing Roadside Safety Hardware Using Manual for Assessing Safety Hardware (MASH) Criteria explores the safety performance of widely used non-proprietary roadside safety features by using MASH. Examples of features evaluated include longitudinal barriers (excluding bridge railings), terminals and crash cushions, transitions, and breakaway supports.The complete report on the project that developed NCHRP RRD 349 was published as NCHRP Web-Only Document 157.
Keywords: Transportation and Infrastructure

Review of Closure Plans for the Baseline Incineration Chemical Agent Disposal Facilities - National Research Council (The National Academies Press, 2010)
This book responds to a request by the director of the U.S. Army Chemical Materials Agency (CMA) for the National Research Council to examine and evaluate the ongoing planning for closure of the four currently operational baseline incineration chemical agent disposal facilities and the closure of a related testing facility. The book evaluates the closure planning process as well as some aspects of closure operations that are taking place while the facilities are still disposing of agent. These facilities are located in Anniston, Alabama; Pine Bluff, Arkansas; Tooele, Utah; and Umatilla, Oregon. They are designated by the acronyms ANCDF, PBCDF, TOCDF, and UMCDF, respectively. Although the facilities all use the same technology and are in many ways identical, each has a particular set of challenges.
Keywords: Environment and Environmental Studies

Review of the Environmental Protection Agency's Draft IRIS Assessment of Tetrachloroethylene - National Research Council (The National Academies Press, 2010)
Tetrachloroethylene is a volatile, chlorinated organic hydrocarbon that is widely used as a solvent in the dry-cleaning and textile-processing industries and as an agent for degreasing metal parts. It is an environmental contaminant that has been detected in the air, groundwater, surface waters, and soil. In June 2008, the U.S. Environmental Protection Agency released its draft Toxicological Review of Tetrachloroethylene (Perchloroethylene) (CAS No. 127-18-4) in Support of Summary Information on the Integrated Risk Information System (IRIS). The draft IRIS assessment provides quantitative estimates of cancer and noncancer effects of exposure to tetrachloreothylene, which will be used to establish airquality and water-quality standards to protect public health and to set cleanup standards for hazardous waste sites. At the request of EPA, the National Research Council conducted an independent scientific review of the draft IRIS assessment of tetrachloroethylene from toxicologic, epidemiologic, and human clinical perspectives. The resulting book evaluates the adequacy of the EPA assessment, the data and methods used for deriving the noncancer values for inhalation and oral exposures and the oral and inhalation cancer unit risks posed by tetrachloroethylene; evaluates whether the key studies underlying the draft IRIS assessment are of requisite quality, reliability, and relevance to support the derivation of the reference values and cancer risks; evaluates whether the uncertainties in EPA's risk assessment were adequately described and, where possible, quantified; and identifies research that could reduce the uncertainty in the current understanding of human health effects associated with tetrachloroethylene exposure.
Keywords: Environment and Environmental Studies

Review of Canadian Experience with the Regulation of Large Commercial Motor Vehicles - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 671: Review of Canadian Experience with the Regulation of Large Commercial Motor Vehicles examines the process used in Canada to harmonize heavy truck size and weight regulations across the country. The report provides insights on how lessons learned from the Canadian experience might be applied in the United States.
Keywords: Transportation and Infrastructure

Review of the Federal Railroad Administration Research and Development Program: Letter Report February 2010 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Committee for Review of the Federal Railroad Administration (FRA) Research and Development (R&D) Program has issued its third letter report to Joseph Szabo, Administrator, U.S. Federal Railroad Administration. The committee believes that FRA’s previous research agenda needs to be replaced by a new strategic R&D plan that aligns project priorities with the new realities facing the railroad industry.The new realities include rapid changes in the railroad industry’s external market environment and the dramatic shift in rail passenger service priorities as a result of new federal legislation and funding. Broadly, the committee recommends that FRA and the U.S. Department of Transportation (USDOT) define what must be done both technologically and economically to make higher-speed, safer, and more convenient, accessible, and reliable rail passenger services possible.
Keywords: Transportation and Infrastructure

Review of the Department of Defense Enhanced Particulate Matter Surveillance Program Report - National Research Council (The National Academies Press, 2010)
Soldiers deployed during the 1991 Persian Gulf War were exposed to high concentrations of particulate matter (PM) and other airborne pollutants. Their exposures were largely the result of daily windblown dust, dust storms, and smoke from oil fires. On returning from deployment, many veterans complained of persistent respiratory symptoms. With the renewed activity in the Middle East over the last few years, deployed military personnel are again exposed to dust storms and daily windblown dust in addition to other types of PM, such as diesel exhaust and particles from open-pit burning. On the basis of the high concentrations observed and concerns about the potential health effects, DOD designed and implemented a study to characterize and quantify the PM in the ambient environment at 15 sites in the Middle East. The endeavor is known as the DOD Enhanced Particulate Matter Surveillance Program (EPMSP). The U.S. Army asked the National Research Council to review the EPMSP report. In response, the present evaluation considers the potential acute and chronic health implications on the basis of information presented in the report. It also considers epidemiologic and health-surveillance data collected by the USACHPPM, to assess potential health implications for deployed personnel, and recommends methods for reducing or characterizing health risks.
Keywords: Health and Medicine; Environment and Environmental Studies